Praktik Pencabutan Pembebasan Bersyarat Pada Narapidana Residivis di Rutan Kelas IIB Pangkalan Brandan - Iana Tresia A Sibagariang; Raja Ritonga (Universitas Sang Bumi Ruwa Jurai, 2023)
The Class IIB State Detention Pangkalan Brandan is Technical Implementation Unit that has duties and functions of Corrections in accordance based Law Number 22 of 2022 concerning of Corrections. Even though did service for prisoner, The Class IIB State Detention Pangkalan Brandan also provides service for inmates, one of which is Parole program consisting of Conditional Exemption (PB). Conditional Exemption (PB) is more likely to be revoked due to the long probation period. When Conditional Exemption (PB) got released, the inmates who violate general conditions and special conditions in accordance with the provisions of the Minister of Law and Human Rights Regulation Number 7 of 2022 can be revoked. This research type of normative legal was carried out to answer the process of revocation of Conditional Exemption and get the accurate results by drawing from several sources. In the case of revocation of Conditional Exemption, it starts sending a request letter by Class IIB State Detention Pangkalan Brandan Officer then examined by the Community Counselor (PK) to be brought to the Correctional Observation Team session so that the results are reported to the Director General via SPION. The decision to revoke Conditional Exemption is conveyed to the prison and state detention officer to be implemented in accordance with the decision. However, the revocation of Conditional Exemption have problems.